Trees for life: The ecosystem service contribution of trees to food production and livelihoods in the tropics - Reed, J.D.; Vianen, J. van; Foli, S.; Clendenning, J.; Yang, K.; MacDonald, M.; Petrokofsky, G.; Padoch, Christine; Sunderland, Terry C.H. (Elsevier, 2017)
Despite expanding interest in ecosystem service research over the past three decades, in-depth understanding of the contribution of forests and trees to food production and livelihoods remains limited. This review synthesizes the current evidence base examining the contribution of forest and trees to agricultural production and livelihoods in the tropics, where production often occurs within complex land use mosaics that are increasingly subjected to concomitant climatic and anthropogenic pressures. Using systematic review methodology we found 74 studies investigating the effect of forest or tree-based ecosystem service provision on a range of outcomes such as crop yield, biomass, soil fertility, and income. Our findings suggest that when incorporating forests and trees within an appropriate and contextualized natural resource management strategy, there is potential to maintain, and in some cases, enhance yields comparable to solely monoculture systems. Furthermore, this review has illustrated the potential of achieving net livelihood gains through integrating trees on farms, providing rural farmers with additional income sources, and greater resilience strategies to adapt to market or climatic shocks. However, we also identify significant gaps in the current knowledge that demonstrate a need for larger-scale, longer term research to better understand the contribution of forest and trees within the broader landscape and their associated impacts on livelihoods and food production systems.